2020
DOI: 10.12785/ijcds/090204
|View full text |Cite
|
Sign up to set email alerts
|

Efficient algorithm for malware classification: n-gram MCSC

Abstract: In this paper, we proposed n-gram MCSC. This method extracts n-gram opcode from execution file and use Simhash to make image of them. We measured and compared the performance metrics of n-gram MCSC and existing MCSC such as accuracy, loss, precision and AUC value of PR curve and ROC curve. To verify whether the difference of accuracy is significant statistically or not, we made experiments of it thirty times and did the ANOVA analysis. We found it was significant. As the result of post-hoc analysis, n-gram MCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Authors in [40] suggested an n-gram approach for detecting malware samples; even though such an approach is intuitive, yet it computational costs are unbearable. Thus, most researchers utilize machine learning classifiers to detect malicious software by encoding the given sample into a feature vector and passing it to a trained model.…”
Section: A Related Work On Malware Detectionmentioning
confidence: 99%
“…Authors in [40] suggested an n-gram approach for detecting malware samples; even though such an approach is intuitive, yet it computational costs are unbearable. Thus, most researchers utilize machine learning classifiers to detect malicious software by encoding the given sample into a feature vector and passing it to a trained model.…”
Section: A Related Work On Malware Detectionmentioning
confidence: 99%